Trends in enrollment, retention, and graduation of United States veterinary technicians/nurses schools - Kogan, Lori R.; Jensen, Wayne A. (Frontiers in Veterinary Science, 2024)
Objective There is a significant shortage of veterinary technicians. To help address this issue, there has been a call to increase the capacity of United States VT/N educational programs. Yet, the current challenges within the field may be negatively impacting the number of people deciding to pursue VT/N certification. To assess this possibility, this study was designed to explore the enrollment, retention, and graduation trends within United States VT/N educational programs. Explore the trends between 2018 and 2022 in enrollment, retention, and graduation of veterinary technicians/nurses (VT/N) at educational programs located in the United States. Sample Educators and administrators working in United States VT/N educational programs. Procedures An electronic survey distributed via an anonymous link within emails sent from the Association of Veterinary Technician Educators. Results A total of 82 responses from educators and administrators working in United States VT/N educational programs were received. Forty-three percent of participants indicated a decrease in student enrollment in the last 5 years. The factors seen to have the largest significant impact were “More potential students not convinced being credentialed will lead to a difference in job duties when compared to non-credentialed work,” “More potential students who do not think being credentialed will lead to a substantial increase in pay when compared to non-credentialed work” and “More potential students not willing/able to invest the time needed to become credentialed.” A total of 60% reported an increase in retention efforts within the last 5 years. The services most commonly reported as increasing included mental health support and academic mentoring. Conclusions and clinical relevance This study suggests that an increased number of potential VT/N students are deciding that being credentialed is not worth the time or money. While additional resources directed toward recruitment and retention are needed within VT/N educational programs, without systematic changes within the field, it is likely that there will be a continued decline in the number of interested applicants.